2010
DOI: 10.1089/ten.tec.2009.0795
|View full text |Cite
|
Sign up to set email alerts
|

A Combining Method to Enhance theIn VitroDifferentiation of Hepatic Precursor Cells

Abstract: The ideal bioartificial liver should be designed to reproduce as nearly as possible in vitro the habitat that hepatic cells find in vivo. In the present work, we investigated the in vitro perfusion condition with a view to improving the hepatic differentiation of pluripotent human liver stem cells (HLSCs) from adult liver. Tissue engineering strategies based on the cocultivation of HLSCs with hepatic stellate cells (ITO) and with several combinations of medium were applied to improve viability and differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Initially, the fibroblasts were seeded to allow for the production of the primary ECM molecules necessary for the proliferation and differentiation of endothelial cells. As reported in Figure a–d, and has been demonstrated in previous papers (Zavan et al , ; Carraro et al , ; Bressan et al ., ), fibroblasts secrete both structural and adhesive molecules, such as type I, III, IV and VII collagens, laminin‐1 and ‐5 and fibronectin, into the interstices of the 3D scaffolds.…”
Section: Discussionsupporting
confidence: 86%
“…Initially, the fibroblasts were seeded to allow for the production of the primary ECM molecules necessary for the proliferation and differentiation of endothelial cells. As reported in Figure a–d, and has been demonstrated in previous papers (Zavan et al , ; Carraro et al , ; Bressan et al ., ), fibroblasts secrete both structural and adhesive molecules, such as type I, III, IV and VII collagens, laminin‐1 and ‐5 and fibronectin, into the interstices of the 3D scaffolds.…”
Section: Discussionsupporting
confidence: 86%
“…It is proposed that hMSCs can play a key role in releasing trophic factors, which are important in cell protection and support following injury [25]. In our previous in vitro study, we have already demonstrated that hMSCs support hepatocytes maturation in a bioreactor system [26]. In this work, we additionally proved that also the HA-based scaffold plays a critical role in promoting the proliferation of endothelial cells, especially in the area surrounding the scaffold.…”
Section: Figure 2 (A)supporting
confidence: 57%
“…All 3D-cultures were maintained with DMEM supplemented with 10% FBS, 1% glutamine, and 10 nM dexamethasone in a bioreactor at 37 °C and 5% CO2. The bioreactor consisted in eight independent chambers, as previously described [26]. The seeded HA-based tubes were placed in the bioreactor, one in each separate chamber, where a perfusion medium flow rate of 0.5 mL/min through each scaffold was assured.…”
Section: D-cultures Preparationmentioning
confidence: 99%
“…Evidence for the drug metabolizing activity of both Phase I and Phase II enzymes has been reported for pluripotent stem cell-generated hepatocyte-like cells [36,37,39,40,44,45,[47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Pluripotent Stem Cellsmentioning
confidence: 99%